A Growth and Yield Model for Eucalyptus benthamii in the Southeastern United States - Kevin B Hall; Jl Stape; Bronson P Bullock; Doug Frederick; Jeff Wright; Henrique F Scolforo; Rachel Cook (Forest Science, 2019)
In recent Eucalyptus cold-tolerance trials, E. benthamii has shown good growth rates as well as cold tolerance for USDA Plant Hardiness Zones 8 and 9. This study developed growth and yield models for E. benthamii in the southeastern United States. A network of 182 temporary sample plots of E. benthamii ranging in age from 1.5 to 13.3 years was established, and inventory data were collected. Site quality was determined by fitting a polymorphic site index curve, whereas a function for stand basal area based on age, dominant height, and site occupancy was fitted. Stand-level volume and dry-weight biomass prediction equations were fitted as a function of dominant height and basal area. Based on the growth and yield model results, mean annual increments ranged from 26.4 m3 ha–1 year–1 at rotation age 6 years on the best sites to 13.7 m3 ha–1 year–1 at rotation age 10 years on the poorest sites. This is the first published set of management-oriented models for land managers considering planting E. benthamii in the southeastern United States.

The Global High Frequency Radar Network - Hugh Roarty; Thomas Cook; Lisa Hazard; Doug George; Jack Harlan; Simone Cosoli; Lucy Wyatt; Enrique Alvarez Fanjul; Eric Terrill; Mark Otero; John Largier; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

A high-throughput SNP marker system for parental polymorphism screening, and diversity analysis in common bean (Phaseolus vulgaris L.) - Matthew W. Blair; Andrés J. Cortés; R. Varma Penmetsa; Andrew Farmer; Noelia Carrasquilla-Garcia; Doug R. Cook (Theoretical and Applied Genetics, 2013)

Summary findings of the fourth international radiocarbon intercomparison (FIRI)(1998–2001) - Elisabetta Boaretto; Charlotte Bryant; Israel Carmi; Gordon Cook; Steinar Gulliksen; Doug Harkness; Jan Heinemeier; John McClure; Edward McGee; Philip Naysmith; Goran Possnert; Marian Scott; et al. (Journal of Quaternary Science, 2002)
Interlaboratory comparisons have been widely used in applied radiocarbon science. These are an important part of ongoing quality assurance (QA) programmes, which are vital to the appropriate interpretation of the evidence provided by the 14 C record in Quaternary applications (including climate change and environmental reconstruction). International comparisons of laboratory performance are an essential component of the quality assurance process in radiocarbon dating. If the user community is to have confidence in radiocarbon results, it needs to be assured that laboratories world wide are producing measurements that are reliable and in accordance with ‘good practice’. The findings from the most recent (completed in 2001) and extensive (more than 90 participating laboratories) radiocarbon intercomparison (FIRI) are reported here. This study was designed (i) to assess comparability, or otherwise, of the results from different laboratories and (ii) to quantify the extent and possible causes of any interlaboratory variation. The results demonstrate that there are no significant differences amongst the main measurement techniques (gas proportional counting, liquid scintillation counting and accelerator mass spectrometry (AMS)) but there is evidence of small laboratory offsets relative to known age samples for some laboratories. There is also evidence in some cases of underestimation of measurement precision. Approximately 10% of all results were classified as extreme (outliers) and these results were generated by 14% of the laboratories. Overall, the evidence supports the fact that radiocarbon laboratories are generally accurate and precise but that, notwithstanding internal QA procedures, some problems still occur, which can best be detected by participation in independent intercomparisons such as FIRI, where the results allow individual laboratories to assess their performance and to take remedial measures where necessary. The results from FIRI are significant in that they show a broad measure of agreement between measurements made in different laboratories on a wide range of materials and they also demonstrate no statistically significant difference between measurements made by radiometric or AMS techniques. Copyright © 2002 John Wiley & Sons, Ltd.

Stability in the historical pattern of genetic structure of Newfoundland cod (Gadus morhua) despite the catastrophic decline in population size from 1964 to 1994 - Daniel E. Ruzzante; Christopher T. Taggart; Roger W. Doyle; Doug Cook (Conservation Genetics, 2001)